Ecological functions of zoosporic hyperparasites - Gleason, Frank H.; Lilje, Osu; Marano, Agostina V.; Sime-Ngando, Télesphore; Sullivan, Brooke K.; Kirchmair, Martin; Neuhauser, Sigrid (Frontiers in Microbiology, 2014)
Zoosporic parasites have received increased attention during the last years, but it is still largely unnoted that these parasites can themselves be infected by hyperparasites. Some members of the Chytridiomycota, Blastocladiomycota, Cryptomycota, Hyphochytriomycota, Labyrinthulomycota, Oomycota, and Phytomyxea are hyperparasites of zoosporic hosts. Because of sometimes complex tripartite interactions between hyperparasite, their parasite-host, and the primary host, hyperparasites can be difficult to detect and monitor. Some of these hyperparasites use similar mechanisms as their parasite-hosts to find and infect their target and to access food resources. The life cycle of zoosporic hyperparasites is usually shorter than the life cycle of their hosts, so hyperparasites may accelerate the turnaround times of nutrients within the ecosystem. Hyperparasites may increase the complexity of food webs and play significant roles in regulating population sizes and population dynamics of their hosts. We suggest that hyperparasites lengthen food chains but can also play a role in conducting or suppressing diseases of animals, plants or algae. Hyperparasites can significantly impact ecosystems in various ways, therefore it is important to increase our understanding about these cryptic and diverse organisms.